INFLUENCE OF PRINCIPALS’ DECISION MAKING STRATEGIES ON STUDENTS’ DISCIPLINE IN BAUCHI STATE PUBLIC SECONDARY SCHOOLS, NIGERIA - Prof Mrs V.E Okereke; Okunade Joseph Boluwatife; Anyanwu George (International Journal of Innovations in Engineering Research and Technology, 2021)
The study was conducted to examine the Influence of Principals’ Decision Making Strategies on Students’ Discipline in Bauchi State Public Secondary Schools, Nigeria. The study was guided by seven research questions. This study was based on the Contingency Theory developed by Fielder’s 1970 which says that leaders’ ability to lead is contingent upon various situational factors. Descriptive research design was used in this study and Proportional stratified random sampling techniques was applied to select the participant. The sample comprised of 20 principals drawn from the three educational zones in Bauchi. The instrument for data collection was measure on a modified 5 point likert scale named the principals decision making strategies and students discipline questionnaire (PDMASDQ). Data was analysed using mean and standard deviation to answer the seven research questions while T-test was used to test the hypotheses. The result of the study revealed that (i) to a moderate extent with grand mean value of 3.8 the principals recognise the problem first before making decision. (ii).to a moderate extent he analyse the information before making decision with mean grand mean value of 3.3 (iii)to moderate extent the principal develop alternative solution which influence students discipline (iv)to a moderate extent he evaluate the alternative solution which influence students discipline (v)to a moderate extent the principal select the best alternative with the grand mean value of 3.3 (vi) to a moderate extent the principal implement decision and it influence students discipline. (vii) to a large extent the principal evaluate and control the decision which influence students discipline. It was recommended among others that: principals should identify the root of problems in school before making decision, principals should plan ahead for the student, principals should allow teachers to exercise their duties freely without any restriction, Students should be sensitized on the importance of adherence to school rules and regulations, principals should always evaluate the decision made and check the effect on student discipline. This will go a long way in guaranteeing respect to the leaders.